2020
DOI: 10.3390/s20226669
|View full text |Cite
|
Sign up to set email alerts
|

Towards Automated 3D Inspection of Water Leakages in Shield Tunnel Linings Using Mobile Laser Scanning Data

Abstract: On-site manual inspection of metro tunnel leakages has been faced with the problems of low efficiency and poor accuracy. An automated, high-precision, and robust water leakage inspection method is vital to improve the manual approach. Existing approaches cannot provide the leakage location due to the lack of spatial information. Therefore, an integrated deep learning method of water leakage inspection using tunnel lining point cloud data from mobile laser scanning is presented in this paper. It is composed of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…These equations are built under the assumption that the geometry of a tunnel can be modeled by a cylinder, and this assumption is valid because the deformation of a tunnel compared with the size of it is negligible. 51,55 The specific procedure of this warped method contains three steps. First, each pixel in the stitched image is converted to a point in the center of a grid of the custom 2D RGB point cloud (Figure 18).…”
Section: Image Mosaicingmentioning
confidence: 99%
See 2 more Smart Citations
“…These equations are built under the assumption that the geometry of a tunnel can be modeled by a cylinder, and this assumption is valid because the deformation of a tunnel compared with the size of it is negligible. 51,55 The specific procedure of this warped method contains three steps. First, each pixel in the stitched image is converted to a point in the center of a grid of the custom 2D RGB point cloud (Figure 18).…”
Section: Image Mosaicingmentioning
confidence: 99%
“…In order to provide a larger field of 3D view, the image is warped according to the following equations: x=()π2θ×R y=y=H z=R θ=π2()WP/2×AR where ( x ′, y ′, z ′) is the coordinate in Cartesian coordinates; ( H , W ) is the coordinate in image coordinates (Figure 17); P is the total number of pixels of the image along the W direction; A is the precision of pixel (0.3 mm/pixel in this study); and R is the inner radius of the tunnel lining. These equations are built under the assumption that the geometry of a tunnel can be modeled by a cylinder, and this assumption is valid because the deformation of a tunnel compared with the size of it is negligible 51,55 …”
Section: Image Mosaicingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors 2021, 21, x FOR PEER REVIEW 21 of 25 et al [55]), the area, and the volume of the identified spalling defect are accurately quantified and outputted. This automated spalling inspection approach can significantly aid with tunnel structural health monitoring and improve the digital management of railway tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…Containing a large quantity of joints, holes and other weak points, shield tunnels are very likely to encounter the hazards of sand gushing and water leakage, especially for tunnels in water-rich sandy stratum [1,2]. These hazards could affect the normal operation of the tunnel, or even endanger the safety of the tunnel structure, and cause engineering accidents [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%